Effects of hot-air fluidized-bed drying on cooking quality, antioxidant activity and bioactive compounds in germinated brown rice - Taechapairoj, Chaiyong; Kaewyot, Krittanai (Science, Engineering and Health Studies, 2020)
Germinated brown rice (GBR) is a nutrition-added product that gains much interest from consumers in Thailand. Drying GBR helps prolonging product shelf-life for the commercial production. However, it could bring about loss in some quality aspects. Therefore, this work investigated the effects of drying on physical quality, cooking quality, antioxidant activity and bioactive compounds of germinated paddy using fluidized-bed dryer. The germinated paddy rice (Phitsanulok 2 variety) with the initial moisture content of 48.5% (dry basis) was dried using a fluidized-bed dryer at the temperature of 110-150°C to obtain the moisture content of 19-21%. Experimental results showed that the head rice yield and the cooking time increased but the solid loss and the volume expansion decreased with increasing drying temperatures. The water uptake and the volume expansion were drying temperature independence. The amylose-lipid complex in GBR, determined by X-ray diffractometry, was discovered when drying in the hot-air temperature of 110°C and 130°C but not the temperature of 150°C. The total phenolic content, the ferric reducing antioxidant power and the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity of GBR were close to those of the reference GBR. Moreover, the drying temperature did not influence the γ-aminobutyric acid and the gamma-oryzanol content of the GBR. The study indicated the advantage of hot-air fluidized-bed drying in preserving antioxidative capacities and nutritional values of GBR.